Effective Family Support : Responding to What Parents Tell Us. - Burgess, Cheryl (Protecting Children and Young People Ser., 2017)
A practical guide to assist staff in supporting families who need help with the task of parenting their children. This support may be required because families are lacking informal networks of support or because of professionals’ worries about the levels of care parents or carers are providing for their children. The co-authors are experienced practitioners in family support and their book offers practical advice and useful suggestions for approaches to and ways of offering support. It is written and presented in a readable way, using day-to-day language which steers clear of social work jargon and terminology.There is a section on the theoretical underpinnings of the work with clear links made to their relevance to practice.The book offers unique insights as it is directly relared to research with parents. It reflects the findings from research studies across a wide range of contexts including studies about child neglect, supporting children affected by parental substance misuse, nurture groups in nurseries and the use of Public Social Partnerships in early intervention with families. It is thus an invaluable practice guide to social workers, teachers, health visitors and youth workers and others working directly with families--from publisher's website